Cadmium Accumulation in Some Organs of Rana Ridibunda Ridibunda Affect Erythrocytic Nuclear Abnormalities - Baker, Semaa Ahmad; Alhaaik , Ammar Ghanim; Mohammed-Ali , Hussein Sabir; Ali , Talib Hussein (International Journal of Scientific Research in Biological Sciences, 2025)
n the current research, accumulation of cadmium was investigated in various organs kidney, liver and the testis of Ranaridibunda exposed to diverse experimental levels of cadmium and erythrocytic abnormalities. Rana ridibunda species inhabits small shallow streams located in North Mosul / Iraq. Although cadmium level was not detectable in source water and expected to be with quality water guideline levels to protect the life in fresh freshwater proposed by the Agency of environmental protection (EPA), therefore the noticeable Cd level detected in experimental animals could pose danger to aquatic organisms. The Cd concentration in the different frog tissues was variable, the highest concentration was found in testis and the lowest in the liver. Frogs from treated groups had significantly higher hepatic (1.3232 2.1800, 3.5130 μg / g), renal (3.4556, 4.2850, 4.9992 μg /g) and testicular (3.5812, 4.8170, 5.5556 μg / g ) for 2.5, 5 and 10 Cd / µg /L respectively than those from the control group (1.0718, 1.9678, 3.2290 μg / g). There was erythrocytic nuclear abnormalities which significantly higher in number of Micronuclei (MN), notched nuclei (N), Lobed nuclei (L) and nuclei with kidney shaped (K) respectively were noted in the groups for 2.5 and 5 Cd / µg /L treated groups than that from natural sites, also with higher frequency significantly of immature erythrocyte with deleterious effect and totally erythrocytes demolished at 10 Cd / µg /g. This research found that cadmium accumulation of the different treatments frogs have higher in testicular, renal, hepatic and found a higher number of erythrocytic nuclear abnormalities when compared to frogs from natural habitat. Therefore, the accumulation of cadmium in the tissues that are used with concentrations and sampling periods is taken into consideration.